THE MARKETING STRATEGIES & IMPROVED OPTIMIZATION OF COMPETENCE OF ENTREPRENEURSHIP: SURVEY OF SMALL AND MEDIUM BUSINESS IN INDONESIA CERAMIC ICONIC PRODUCTS - Dede Romlah Oktini (SAMPURASUN, 2019)
This study was conducted to determine the effect of market strategy, marketing mix strategy and entrepreneurial competencies to competitive advantage of marketing and its implications on the performance of ceramic iconic product marketing in West Java. The total sample of 220 respondents, the owners of small and medium-scale ceramic enterprises in West Java. The sampling method used power analysis techniques. Data collected through observation, interviews and surveys using questionnaires instrument closed and open. The analytical method used is Structural Equation Model. The results found that the influence of the entire independent variables significantly influence the intervening variable, and the effect of intervening variables significantly influence the independent variable. The amount of direct influence on competitive advantage strategy marketing market by 3.8%, the magnitude of the direct influence of marketing mix strategy on competitive advantage of marketing at 11.5%, the magnitude of the direct influence of entrepreneurial competencies to competitive advantage of marketing by 15.6%. The magnitude of the direct effect of the competitive advantage of marketing to marketing performance by 9.1%. Sequentially important variable is the competence of entrepreneurship, marketing mix strategy, market strategy, marketing competitive advantage. Marketing competitive advantage is influenced by market strategy, marketing mix strategy and entrepreneurial competence by 65%, while the remaining 35% are influenced by other factors (ceteris paribus). To 5 hypothesis proposed in this study were all found